Pemetaan dan pengembangan potensi Desa Mapur Kecamatan Bintan Pesisir Kabupaten Bintan Provinsi Kepulauan Riau - Teguh Setiandika Igiasi; Atika Thahira; Reza Gumilang; Dedy Afrizal; Dina Purnamasari (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The community service program conducted in Mapur Village, Bintan Pesisir District, Bintan Regency, represents a concrete effort to address various strategic challenges faced by local communities in optimizing their regional potential. This program was implemented through a series of systematic stages involving active participation from both the community and local stakeholders. The main objective of this activity was to map and develop the potentials of Mapur Village through a participatory approach that positions the community as the primary agents of development. The methods employed included field observation, Focus Group Discussions (FGD), pre-tests, and post-tests to assess the community’s level of understanding regarding their local potentials. The pre-test results indicated that only about 5% of the population were aware of existing potentials beyond the fisheries and tourism sectors. The study further identified several other promising potentials, such as local culinary industries, handicrafts and the creative economy, youth involvement, and the contribution of migrant villagers, all of which play strategic roles in driving economic and social development. Therefore, community-based potential mapping serves as an essential foundation for realizing an independent, competitive, and sustainable rural development model in coastal areas.